Gender differences in substrate utilization during submaximal exercise in endurance-trained subjects - Roepstorff, C.; Steffensen, C. H.; Madsen, M.; Stallknecht, B.; Kanstrup, I. L.; Richter, E. A.; Kiens, B. (American Journal of Physiology, Endocrinology and Metabolism, 2002)
Substrate utilization across the leg during 90 min of bicycle exercise at 58% of peak oxygen uptake (VO(2 peak)) was studied in seven endurance-trained males and seven endurance-trained, eumenorrheic females by applying arteriovenous catheterization, stable isotopes, and muscle biopsies. The female and male groups were matched according to VO(2 peak) per kilogram of lean body mass, physical activity level, and training history of the subjects. All subjects consumed the same diet, well controlled in terms of nutrient composition as well as energy content, for 8 days preceding the experiment, and all females were tested in the midfollicular phase of the menstrual cycle. During exercise, respiratory exchange ratio (RER) and leg respiratory quotient (RQ) were similar in females and males. Myocellular triacylglycerol (TG) degradation was negligible in males but amounted to 12.4 +/- 3.2 mmol/kg dry wt in females and corresponded to 25.0 +/- 6.0 and 5.0 +/- 7.3% of total oxygen uptake in females and males, respectively (P < 0.05). Utilization of plasma fatty acids (12.0 +/- 2.5 and 9.6 +/- 1.5%), blood glucose (13.6 +/- 1.5 and 14.3 +/- 1.5%), and glycogen (48.5 +/- 4.9 and 42.8 +/- 2.1%) were similar in females and males. Thus, in females, measured substrate oxidation accounted for 99% of the leg oxygen uptake, whereas in males 28% of leg oxygen uptake was unaccounted for in terms of measured oxidized lipid substrates. These findings may indicate that males utilized additional lipid sources, presumably very low density lipoprotein-TG or TG located between muscle fibers. On the basis of RER and leg RQ, it is concluded that no gender difference existed in the relative contribution from carbohydrate and lipids to the oxidative metabolism across the leg during submaximal exercise at the same relative workload. However, an effect of gender appears to occur in the utilization of the different lipid sources.